Remote ischaemic conditioning and early changes in plasma creatinine as markers of one year kidney graft function-A follow-up of the CONTEXT study. - Marie B Nielsen; Nicoline V Krogstrup; Mihai Oltean; Gertrude J Nieuwenhuijs-Moeke; Frank J M F Dor; Henrik Birn; Bente Jespersen (PLoS ONE)
Background Ischaemia-reperfusion injury in kidney transplantation leads to delayed graft function (DGF), which is associated with reduced long term graft function. Remote ischaemic conditioning (RIC) improved early kidney graft function in a porcine model of donation after brain death and was associated with improved long-term cardiac outcome after myocardial ischaemia. This randomised, double-blinded trial evaluated the effect of RIC on kidney graft outcome in the first year, and examined the predictive value of a new measure of initial kidney graft function, i.e. the estimated time to a 50% reduction in plasma creatinine post-transplantation (tCr50). Methods A total of 225 patients undergoing deceased donor kidney transplantation were randomised to RIC or a sham procedure performed prior to kidney reperfusion. Up to four repetitive cycles of five minutes of leg ischaemia and five minutes of reperfusion were given. GFR, plasma creatinine, cystatin C and neutrophil gelatinase associated lipocalin (NGAL) were measured at three and twelve months and estimated GFR was calculated using four different equations. Other secondary outcomes were identified from patient files. Results RIC did not affect GFR or other outcomes when compared to the sham procedure at three or twelve months. tCr50 correlated with one year graft function (p<0.0001 for both mGFR and eGFR estimates). In contrast, DGF i.e. "need of dialysis the first week" did not correlate significantly with one year GFR. Conclusion RIC during deceased donor kidney transplantation did not improve one year outcome. However, tCr50 may be a relevant marker for studies aiming to improve graft onset. Trial registration www.ClinicalTrials.gov Identifier: NCT01395719.